2014
DOI: 10.15389/agrobiology.2014.5.28eng
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Initial Steps of Potato Virus X Assembly

Abstract: A b s t r a c tPotato virus X (Potexvirus) is an important pathogen of number of economically significant agricultural plants of the Solanaceae family. Potato virus X (PVX) virions are flexible filamentous particles 515 nm in length and 13.5 nm in diameter with a helical structure. PVX genome consists of a single-stranded RNA (6435 nucleotides) which is capped and polyadenylated. The study of various stages of the infection process of plant viruses during infection, including the assembly of viral particles is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…7A). The lack of interaction between MNPs and the vRNP head surface may be explained by the competitive binding of all [13]. An analysis of these complexes revealed that most MNPs, upon removal of free RNA, interact with the ends of MN-treated vRNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7A). The lack of interaction between MNPs and the vRNP head surface may be explained by the competitive binding of all [13]. An analysis of these complexes revealed that most MNPs, upon removal of free RNA, interact with the ends of MN-treated vRNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of TMV and AltMV CP (VLP) repolymers and PVX vRNPs TMV and AltMV CP repolymers were prepared using the techniques described in [11,12], respectively; PVX vRNPs were obtained according to [13].…”
Section: Methodsmentioning
confidence: 99%
“…[ 37 ] RNA analysis was carried out using electrophoresis in 1% agarose gel according to. [ 38 ] The gel images were obtained under UV‐illumination using the same gel‐documenting system. The absorption spectra of TMV RNA were measured using NanoDrop 200 (Thermo Scientific, USA) in a wavelength region of λ = 220–350 nm.…”
Section: Methodsmentioning
confidence: 99%